Correlation risk analysis of serum inflammatory factors and 25-hydroxyvitamin D in vascular lesions in type 2 diabetes patients: Serum inflammatory factors and 25-hydroxyvitamin D in T2DM - Zhang, Qian; Zhu, Yuyan; Li, Hui; Wu, Xue; Wu, Cheng; Li, Guang; Yang, Chao (Journal of Medical Biochemistry, 2025)
Objective: To explore the relationships between the levels of serum inflammatory factors and 25-hydroxyvitamin D and diabetic vascular lesions in patients with type 2 diabetes mellitus (T2DM).Methods: A total of 362 adult (aged ≥18 years) patients with type 2 diabetes mellitus (T2DM) who were hospitalized in our hospital from April 2022 to June 2024 were selected as research subjects. The general information of the patients, including sex, age, disease duration, body mass index (BMI), systolic blood pressure (SBP), and diastolic blood pressure (DBP), was collected. The levels of blood parameters, glycated hemoglobin (HbA1c), fasting blood glucose (FPG), total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), inflammatory factors [C-reactive protein (CRP), interleukin-6 (IL-6)], and 25-hydroxyvitamin D [25(OH) D] were determined. The systemic immune inflammation index (SII) and homeostasis model assessment of insulin resistance index (HOMA-IR) were calculated. The vascular lesions were divided into three groups: the simple T2DM group (155 patients), the T2DM microvascular lesion group (122 patients), and the T2DM macrovascular lesion group (85 patients). One-way analysis of variance, the Kruskal‒Wallis H test or the χ2 test were used for comparisons among multiple groups. Spearman correlation analysis was used to analyze the correlation between 25(OH) D and various inflammatory indicators, and multivariate logistic regression analysis was used to analyze the influencing factors of diabetic vascular lesions.Results: The levels of 25(OH) D in both the T2DM microvascular lesion group and the T2DM macrovascular lesion group were significantly lower than those in the simple T2DM group (P
Keywords: Correlation risk analysis; Serum inflammatory factor; 25-hydroxyvitamin D; Vascular lesions; Type 2 diabetes